Enhancing the cytotoxicity of immunotoxins by facilitating their dissociation from target receptors under the reducing conditions of the endocytic pathway - Lee, Hyun Jin; Chae, Byeong Ho; Ko, Deok Han; Lee, Seul Gi; Yoon, Sang Rok; Kim, Dae Seong; Kim, Yong Sung (International Journal of Biological Macromolecules, 2024)
Immunotoxins (ITs) are recombinant chimeric proteins that combine a protein toxin with a targeting moiety to facilitate the selective delivery of the toxin to cancer cells. Here, we present a novel strategy to enhance the cytosolic access of ITs by promoting their dissociation from target receptors under the reducing conditions of the endocytic pathway. We engineered monobodySS, a human fibronectin type III domain-based monobody with disulfide bond (SS)-containing paratopes, targeting receptors such as EGFR, EpCAM, Her2, and FAP. MonobodySS exhibited SS-dependent target receptor binding with a significant reduction in binding under reducing conditions. We then created monobodySS-based ITs carrying a 25 kDa fragment of Pseudomonas exotoxin A (PE25), termed monobodySS-PE25. These ITs showed dose-dependent cytotoxicity against target receptor-expressing cancer cells and a wider therapeutic window due to higher efficacy at lower doses compared to controls with SS reduction inhibited. ERSS/28-PE25, with a KD of 28 nM for EGFR, demonstrated superior tumor-killing potency compared to ER/21-PE25, which lacks an SS bond, at equivalent and lower doses. In vivo, ERSS/28-PE25 outperformed ER/21-PE25 in suppressing tumor growth in EGFR-overexpressing xenograft mouse models. This study presents a strategy for developing solid tumor-targeting ITs using SS-containing paratopes to enhance cytosolic delivery and antitumor efficacy.
Keywords: Disulphide bond-dependent binding; Disulphide bonds; Endocytic pathways; Endosome escape; Endosomes; Immunotoxins; Monobody; Reducing conditions; Target receptor; Therapeutic window; ADP Ribose Transferases; Animals; Bacterial Toxins; Cell Line, Tumor; Endocytosis; Exotoxins; Female; Humans; Immunotoxins; Mice; Oxidation-Reduction; Pseudomonas aeruginosa Exotoxin A; Xenograft Model Antitumor Assays; Disulfide bond-dependent binding; Endosome escape; Immunotoxin; Monobody; Therapeutic window